2015
DOI: 10.1016/j.eats.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step Arthroscopic Assessment of the Anterolateral Ligament of the Knee Using Anatomic Landmarks

Abstract: New insights into the existence and function of the anterolateral ligament (ALL) of the knee have redirected and refocused attention on the secondary restraints of rotational stability of the knee. The importance of assessing the ALL is increasing, especially in anterior cruciate ligament reconstruction surgery, to decide on the need for an adjunctive extra-articular reconstruction of the ALL to control rotational instability of the knee. However, preoperative assessment of this ligament is difficult. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Two studies developed a technique for identifying the ALL arthroscopically. 103,127 Both studies viewed the ALL from the lateral gutter and used the popliteus tendon and lateral collateral ligament as arthroscopic landmarks. Sonnery-Cottet et al 103 confirmed ALL identification by arthroscopically marking the structures with a suture anchor in a cadaveric model.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies developed a technique for identifying the ALL arthroscopically. 103,127 Both studies viewed the ALL from the lateral gutter and used the popliteus tendon and lateral collateral ligament as arthroscopic landmarks. Sonnery-Cottet et al 103 confirmed ALL identification by arthroscopically marking the structures with a suture anchor in a cadaveric model.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have described the possibility of arthroscopic identification of ALL and have provided step-by-step descriptions[ 35 ]. According to Zein[ 35 ], it is possible to identify it with a 30° scope through the AL portal. It is necessary to place the limb in a figure of-4-position.…”
Section: Identification Of Allmentioning
confidence: 99%
“…Recent publications have rediscovered this ligament through classical anatomical dissection studies [3], MRI studies [11, 38] and studies combining dissection and ultrasonography [2]. Intra‐operative descriptions of the ALL have also been made [46, 57].…”
Section: Figmentioning
confidence: 99%